Adsolubilisation of thiacloprid pesticide into the layered zinc hydroxide salt intercalated with dodecyl sulphate, for controlled release formulation. (28th July 2020) - Muda, Zuhailimuna; Hashim, Norhayati; Md Isa, Illyas; Mustafar, Suzaliza; Bakar, Suriani Abu; Mamat, Mazidah; Hussein, Mohd Zobir
ABSTRACT: Sodium dodecyl sulphate surfactant was intercalated into the layered zinc hydroxide salt for the successful adsolubilisation of poor water-soluble pesticide, thiacloprid. The intercalation of the dodecyl sulphate ion was confirmed by PXRD analysis with basal spacing 30.1 Å. The presence of thiacloprid into the interlayer gallery of zinc layered hydroxide also supported with Fourier transform infrared spectra and elemental analysis. Based on the thermal study, thiacloprid was thermally stable after the adsolubilisation compared to its solid form. The release of thiacloprid anions from the nanocomposite into an aqueous solution of sodium phosphate was governed by first-order kinetics. Whereas the release of thiacloprid into sodium sulphate and sodium chloride solution governed by parabolic diffusion kinetics model. In consideration of the obvious breakthrough made in the nanocomposite characterisation and release study, this nanocomposite could be a promising candidate for the profitable improvement of an environment-friendly pesticide formulation.